Larvicidal Efficacy of Citrus sinensis Extracts against Culex quinquefasciatus - Sattar, Maria; Iqbal, Muhammad Naeem; Ashraf, Asfa; Ali, Shahzad; Shahzad, Mirza Imran; Alam, Saman; Ali, Taimoor; Sheikh, Rabia (PSM Microbiology, 2016)
This study was planned to evaluate the larvicidal effect of Citrus sinensis on the fourth instar larvae of Culex quinquefasciatus. Different concentrations of aqueous extracts of peel and leaves of Citrus sinensis were prepared. The mortality rates of larvae were observed after each 24 h of exposure. All the graded concentrations (2%, 3%, 4%) of both peel and leaf extracts showed significant (p<0.05) larvicidal activity. But 4% concentration of peel extract proved to be most effective as it took least time (5 days) to give 100% mortality. No mortality was observed in control group. The results showed that Citrus sinensis as a potential bio control agent against Culex quinquefasciatus due to its larvicidal effect and could be used as an ecofriendly approach for the control of the mosquito.